Targeting Phosphatases and Kinases: How to Checkmate Cancer - Turdo, Alice; D’Accardo, Caterina; Glaviano, Antonino; Porcelli, Gaetana; Colarossi, Cristina; Colarossi, Lorenzo; Mare, Marzia; Faldetta, Naida; Modica, Chiara; Pistone, Giuseppe; Bongiorno, Maria Rita; Todaro, Matilde; et al. (Frontiers in Cell and Developmental Biology, 2021)
Metastatic disease represents the major cause of death in oncologic patients worldwide. Accumulating evidence have highlighted the relevance of a small population of cancer cells, named cancer stem cells (CSCs), in the resistance to therapies, as well as cancer recurrence and metastasis. Standard anti-cancer treatments are not always conclusively curative, posing an urgent need to discover new targets for an effective therapy. Kinases and phosphatases are implicated in many cellular processes, such as proliferation, differentiation and oncogenic transformation. These proteins are crucial regulators of intracellular signaling pathways mediating multiple cellular activities. Therefore, alterations in kinases and phosphatases functionality is a hallmark of cancer. Notwithstanding the role of kinases and phosphatases in cancer has been widely investigated, their aberrant activation in the compartment of CSCs is nowadays being explored as new potential Achille’s heel to strike. Here, we provide a comprehensive overview of the major protein kinases and phosphatases pathways by which CSCs can evade normal physiological constraints on survival, growth, and invasion. Moreover, we discuss the potential of inhibitors of these proteins in counteracting CSCs expansion during cancer development and progression.